Design of a mobile application for home monitoring of babies with complex congenital heart disease - Castro , David; Pérez-Rivero, Paula; Quintero Lesmes, Doris Cristina; Castro, Javier (Revista Cuidarte, 2022)
• With this app the caregivers will demonstrate competence to monitor the conditions of their baby who has complex congenital heart disease at home. • The use of this app will allow babies participating in the monitoring program to have optimized growth and care. • Management of this app will prevent readmission for major and unforeseen medical events. • This app provides comprehensive pre-discharge education to caregivers. Introduction: Congenital heart diseases are related to heart defects that develop during pregnancy and are present at birth. Children must regularly attend specialized clinical centers for treatment, which includes medical check-ups, hemodynamic procedures, and surgery. Nevertheless, the success of interventions largely depends on the education of parents and caregivers about the symptoms and warning signs that babies with complex congenital heart disease may present during the period between stages. Likewise, it is necessary for caregivers to have tools to face the barriers of the health system, such as, obstacles or delays in obtaining healthcare services. This facilitates timely health care for patients and avoids fatal outcomes or deterioration in quality of life. Materials and Methods: This document presents a system that provides support to patients with complex congenital heart disease in follow-up by a home monitoring program. The system consists of a mobile application that allows parents/caregivers to monitor physiological variables of the patients (weight, intake, and oximetry). The information registered in the application is sent for real-time evaluation by the medical team. Results:The application provides an effective means for sending data and communicating with the medical control center, in addition to offering educational and informative material. In this way, parents/caregivers get constant help and feedback about their baby’s condition. Conclusions: The mobile application could help mitigate the costs of medical care and overcome the limitations of follow-up at home, giving doctors the possibility to see the patient’s evolution and give timely recommendations. How to cite this article: Castro David, Pérez-Rivero Paula, Quintero-Lesmes Doris Cristina, Castro Javier. Design of a mobile application for home monitoring of babies with complex congenital heart disease. Revista Cuidarte. 2022;13(3):e2335. http://dx.doi.org/10.15649/cuidarte.2335